PENGEMBANGAN MEDIA PEMBELAJARAN WEBSITE CHATBOT BERBASIS PEMECAHAN MASALAH PADA MATERI PENYAJIAN DATA UNTUK KELAS IV SEKOLAH DASAR - Fauziah, Anisa; Endang M. Kurnianti; Otib Satibi Hidayat (Efektor, 2022)
This research was conducted to determine the feasibility of the learning media website chatbot based on problem-solving in present data for grade 4 elementary school at SDN Kapuk 05 Pagi. This study used research and development as the research method with four stages 4-D Thiagarajan development model, namely: 1) define, 2) design,3) develop, and 4) disseminate. The product of this research was a website chatbot learning media based on problem-solving in present data for grade IV elementary school. The feasibility level based on the results of the percentage assessment of material experts got 78%, learning media experts got 95.5%, linguists got 85%, the instructional design got 92%, one to one evaluation 90,9%, small group evaluation 84%, field test 82,1%, and teacher response assessment results produced was 93,75 %. Based on this result, it could be concluded that website chatbot learning media based on problem learning achieved the category of “very good” and "very decent" to be used as mathematics learning media for present data.